Effectiveness of Acceptance and Commitment Therapy on Family Functioning and Inefficient Attitudes of Women in Second Marriages - Uosof Taleshi, Zeinab; AkbarZadeh, Nilufar; Rahimi, Azita; Razghandi, Sima; Abasian Soraki , Pardis (Psychology of Woman Journal, 2023)
Objective: The present study aims to determine the effectiveness of Acceptance and Commitment Therapy (ACT) on family functioning and inefficient attitudes of women in second marriages.Methods and Materials:  The research method was a quasi-experimental pre-test and post-test with a control group. The study population consisted of women who were in their second marriage and had sought counseling services in Tehran in 2023. From this population, 30 individuals were selected using convenience sampling and randomly assigned into two groups: an experimental group of 15 and a control group of 15. The instruments used for data collection were questionnaires on family functioning and inefficient attitudes. Participants in the experimental group received ACT for 8 weeks, with one 90-minute session per week, while the control group did not receive any specific intervention.Findings:  Findings indicated that the mean scores of family functioning and inefficient attitudes in the post-test were significantly improved in the experimental group compared to the pre-test.Conclusion: Therefore, Acceptance and Commitment Therapy has an impact on family functioning and the inefficient attitudes of women in second marriages.